Tingkat Kepuasan Layanan Sport Massage Imatora terhadap Atlet KONI Jatim Pon Aceh Sumut 2024 - Imam Khudzaifi Alaf; Joesoef Roepajadi (Student Research Journal, 2024)
This study aims to determine the Satisfaction Level of Imatora Sport Massage Services for KONI East Java Athletes participating in the Aceh-North Sumatra PON 2024. The research employs a descriptive quantitative method with a correlational approach. The population consists of 30 East Java PON athletes undergoing centralized training (Puslatda) at KONI East Java in 2024. Data collection methods include (1) observation, (2) interviews, (3) documentation, and (4) questionnaires. The study uses descriptive quantitative data analysis techniques. The findings, as shown in Table 4.5 regarding satisfaction levels with sport massage services, indicate the following 1 respondent (3%) fell into the strongly disagree category 2 respondents (7%) fell into the disagree category, as they reported a lack of knowledge about sport massage and inconsistency in therapy methods 16 respondents (53%) fell into the agree category, and 11 respondents (37%) fell into the strongly agree category. These positive responses were attributed to the comfort experienced during the massage sessions, which left respondents feeling relaxed and reporting improvements in bodily functions after the therapy. In Table 4.5, satisfaction with service ethics was also evaluated 1 respondent (3%) fell into the strongly disagree category. 4 respondents (13%) fell into the disagree category, noting that masseurs/masseuses need better communication skills to ensure comfort 17 respondents (57%) fell into the agree category, and 8 respondents (27%) fell into the strongly agree category, citing adequate service ethics and satisfaction with the professionalism displayed by the masseurs/masseuses. Based on the data presented, the researcher concludes that the satisfaction level of Imatora’s sport massage services for KONI East Java athletes is very good.